DNA based nanoscale optoelectronic devices enabled by THz driven piezo vibrotronic effect - Samira Fathizadeh; Fatemeh Nemati (Scientific Reports)
Abstract Investigating the piezo-vibrotronics effect in DNA chains, focusing on the interplay between mechanical strain, electronic properties, and photonic interactions paves the way for innovative applications of DNA in nanoscale electronic and optical devices. By applying varying degrees of mechanical deformation to DNA molecules, we observe significant changes in their charge transport properties. Strain-induced polarization within the DNA affects on carrier generation and transport, leading to improved optoelectronic performance. Additionally, photonic excitation under strain conditions demonstrates modulation of electronic responses, highlighting the potential of DNA-based materials in advanced piezo-vibro(photo)tronics devices. I-V characterization and multifractal analysis employ to elucidate these effects, providing a comprehensive understanding of the piezo-phototronics phenomenon in biologic systems.